The distribution of benefits under China's new rural cooperative medical system: evidence from western rural China - Sha Lai; Chi Shen; Yongjian Xu; Xiaowei Yang; Yafei Si; Jianmin Gao; Zhongliang Zhou; Gang Chen (BMC, 2018)
Abstract Background China's New Cooperative Medical Scheme (NCMS) enables insured citizens to enjoy the same benefit package by paying a flat-rate premium. However, it still remains uncertain whether economically disadvantaged enrollees receive insurance benefits that at least match those of non-disadvantaged enrollees. This article, therefore, estimates the distribution of benefits under the NCMS across economic groups and compares the magnitude of economic-related inequity changes in the NCMS benefits. Methods Data were drawn from two-wave large-scale representative and comparable cross-sectional household health survey datasets conducted in Shaanxi Province in 2008 and 2013. In total, 9506 (2008) and 38,010 (2013) NCMS enrollees were included. The benefits from the NCMS are measured in two ways: via the probability of receiving reimbursements and via the absolute amount of the obtained reimbursements. Two-part models were used to estimate the benefit distribution and to adjust benefits for health care needs. Concentration curve, dominance test of the concentration curve, and concentration index (CI) were used to estimate the overall degree of economic-related inequality. The degree of horizontal inequity was estimated via indirectly standardized measures based on the "equal treatment for equal needs" concept. Results Our results indicate that economically affluent groups were more likely to receive reimbursements from the NCMS, and these reimbursements were also higher. Positive need-adjusted CIs for the probability of receiving reimbursements (CIs: 0.2027/0.1056 in 2008/2013) and the absolute amount of reimbursements (CIs: 0.3002/0.1660 in 2008/2013) further suggest the existence of clear pro-rich horizontal inequities in the benefits distribution under the NCMS. Encouragingly, a decreasing trend could be observed from 2008 to 2013, which suggests that horizontal inequities in NCMS benefits that favored the rich decreased over the investigated period, while the level of insurance benefits improved. Conclusions Our study suggests that the benefits of NCMS are concentrated toward economically affluent groups. Although any trade-off between policy feasibility and equity has become a challenge for the formulation of social health insurance funding and benefit packages in developing countries, inequality can be gradually reduced through continuous adjustment of the medical insurance scheme, thus effectively targeting economically disadvantaged enrollees.